Implementation Artificial Intelligence (AI) in HOTS Learning (Higher Order Thinking Skills) to Improve Student Intelligence - Apsariningsih, Kiki; Ramadhani, Khalilah; Hutapea, Muslimin (HIKMAH: JURNAL PENDIDIKAN AGAMA ISLAM, 2025)
The background of this research is the phenomenon of students' lack of critical and creative thinking skills, as well as teachers' lack of ability to develop curricula and learning strategies that align with HOTS principles. The purpose of this research is to determine how the implementation of AI in HOTS learning can improve students' intelligence. This research uses a library research method with data sources from relevant scientific articles and journals. Data collection techniques are carried out by collecting and analyzing data from various sources. Data analysis techniques use content analysis to determine how the implementation of AI in HOTS learning can improve students' intelligence. Research results show that implementing AI in HOTS learning is crucial for improving student intelligence. AI can help enhance students' critical and creative thinking skills, as well as assist teachers in curriculum development and student assessment. AI technologies used in HOTS learning include machine learning, natural language processing, and recommendation systems. Thus, implementing AI in HOTS learning can be an effective solution to enhance students' intelligence and prepare them for future challenges. This research is expected to contribute to the development of education in Indonesia in a more effective and efficient manner.